Partnering for climate change adaptations by Dutch housing associations - Roders, Martin (A+BE | Architecture and the Built Environment, 2015)
Introduction Climate change can no longer be ignored. It is globally recognised that the evidence for climate change is unequivocal and that action needs to be taken in order to address its negative effects. These effects, such as warmer and drier summers and more extreme rainfall, may threaten the quality of life of those living in urban environments. To limit these threats, a number of climate change adaptation measures can be taken to pre-empt the negative effects of climate change. The challenge of increasing the implementation of climate change adaptation measures is addressed in this thesis by engaging the construction sector while focusing on the housing stock that is owned and maintained by Dutch housing associations. By implementing climate change adaptation measures, dwellings will become more resilient to some of the effects of climate change, becoming less vulnerable for damage and ensuring the comfort, safety and quality of life of their occupants. Because housing associations are regarded as societal entrepreneurs, these are expected to use resources and commercial profits to achieve societal aims that are in the common interest, such as making timely adaptations, so that changing climatic conditions cannot threaten the quality of their dwellings. Moreover, there are relatively few housing associations compared to the number of houses they own and maintain. In 2012, there were 381 housing associations that owned and maintained a stock of 2.4 million dwellings, representing 32% of the total Dutch housing stock. This means that approaching the Dutch social rented sector was seen as an effective way of generating a greater societal impact. In the past decade, external influences such as the recent economic crisis and political pressure, have led housing associations to become more cost effective and to make changes in their organisational strategies, which has resulted in the adoption of more integrated project delivery methods, such as partnering. These integrated methods aim to involve the construction sector early in the development of plans so that they can contribute their expertise. This creates a more efficient construction and maintenance process and delivers dwellings of higher quality. The housing associations cannot pre-empt all the effects of climate change alone. For adaptation measures at the neighbourhood level, they are dependent on collaboration with other stakeholders such as municipalities, but there are measures that can be applied at the building level, which falls within their range of influence. An example is the application of lighter colours on building façades in order to reflect radiation and reduce the air temperature close to the façades. The hazards of overflowing sewage systems caused by extreme precipitation can be reduced by applying measures to retain water temporarily, such as ‘green roofs’ or to ensure effective drainage such as open pavements. These measures reduce the peak load on the sewage system. Another effective measure is the use of materials that are not negatively affected by water so that if, despite all the precautionary measures, flooding does occur, the consequences would be less severe. Problem formulation This research assesses the potential of adopting a partnering approach as a governance tool with which to increase the implementation of climate change adaptation measures like those described above. The housing stock owned by Dutch housing associations is taken as a case study. Involving the construction sector through a partnering approach is promising, since construction companies are the ones who carry out the works. Their early commitment reduces the risks of miscommunication or failure and enhances opportunities for innovative solutions. By doing this, not only do housing associations take responsibility for their actions, but the construction sector as a whole gains more responsibility for solving societal challenges and is enabled to co-create solutions that can then be disseminated more easily. The main research question is: How can partnering in construction increase the implementation of climate change adaptation measures in dwellings owned by Dutch housing associations? Research approach and results To formulate an answer to this research question, several separate studies were conducted. First, the characteristics of three types of governance were studied in a literature review, these being hierarchic, market and network governance. Based on these types of governance, many tools have been developed over time, but to increase the implementation of climate change adaptation measures in social housing, not all tools are equally successful, at least not from a theoretical point of view. To improve the implementation of measures, tools could be combined to create a more solid basis for action, and there is room for extra governance tools in the current palette. Based on the literature review on partnering, it was concluded that this could be classified as a combined ‘market’ and ‘network’ type of tool. The market aspect refers to the knowledge of climate change adaptation that is gained by the participating construction companies, which can imply a competitive advantage for them. The network aspect is closely linked to collaboration within a partnering approach. In other contexts, the partnering approach has been shown to remove the barriers of fragmentation in the construction sector; to provide for a more efficient and integral construction process, and to allow for the easier flow of knowledge on climate change adaptation. Next, the current state of knowledge among housing associations was studied with regard to climate change adaptation measures for the housing stock. A content analysis was conducted on the annual reports and policy plans of the 25 largest Dutch housing associations and revealed that they display no awareness of climate change adaptation in their policy documents. As such, they were categorised as ‘unaware’. However, this does not mean that the building stock is not being adapted to climate change, because in the annual reports they state that they have applied climate change adaptation measures, although they do not name these as such. This means that applying adaptation measures is neither impossible nor unrealistic, as long as they are not implemented solely for climate change adaptation purposes, but for other reasons as well, such as energy-efficiency. In contrast to the corporate policy documents, interviews with individual policy-makers showed that housing associations are aware of climate change at a global scale. However, in relation to climate change adaptation measures in their daily work, such as the impact of flooded streets and overheating interiors of dwellings, awareness is low. They could not name many threats or adaptation measures. However, once they had been made aware of the need for such measures, the employees were fairly well capable of assessing them, even though the implementation of measures was evaluated as unfeasible in most cases. The main reason provided was that the housing associations did not have policy guidelines in place for such adaptation measures. Moreover, in many cases there were financial and/or technical barriers that would have to be addressed first. There was a consensus among employees that all the measures would have a positive effect on the comfort of the dwellings. Partnering in construction can help to increase the implementation of adaptation measures because it can overcome many of these challenges. For this reason, the way that housing associations and construction companies carry out refurbishment projects in a partnering approach was also studied. The researcher participated in a knowledge exchange project in which housing associations and construction and maintenance companies had formed dyads and carried out a refurbishment project. They exchanged their experiences on a regular basis through interviews and plenary sessions. In the interviews, employees of housing associations and construction and maintenance companies were asked how they dealt with the success factors for partnering, which were derived from literature. These success factors were trust, leadership, partner capabilities, commitment, conflict resolution, coordination and communication. Although they did not address all these success factors equally well, the study showed that Dutch housing associations and construction and maintenance companies are indeed capable of carrying out housing refurbishment projects in a partnering approach. This allows for the selection of the construction process as a governance tool with which to implement climate change adaptation measures. These measures are considered new products that can be installed with the aim of improving the technical and functional quality of dwellings. In that sense, they are perceived as product innovations, with the dwellings being the ‘products’ and/or assets of the housing associations. This perspective corresponds with the definition1: “[An innovation is] a new idea that is implemented in a construction project with the intention of deriving additional benefits although there might have been associated risks and uncertainties. The new idea may refer to new design, technology, material component or construction method deployed in a project”. Subsequently, the employees of the housing associations and construction and maintenance companies were asked how they dealt with the implementation of innovations using surveys. Although several studies indicate that innovation can benefit when projects are based on an integrated construction process such as partnering, the current study concludes that partnering does not automatically lead to product innovation. Most of the respondents saw partnering itself as the innovative aspect of their projects – i.e. a process innovation. That process innovation required so much attention that there was less emphasis on opportunities for product innovations. This should be taken into account when developing governance tools to encourage the implementation of product innovations in dwellings such as climate change adaptation measures. Moreover, the choice of partnering as a project delivery method as a governance tool is less likely to resolve issues regarding policy, which remain a barrier for the implementation of measures. In addition, other parties can also become involved, to generate resources for the implementation of measures by housing associations. The adoption of partnering as a project delivery method is therefore not the only possible governance tool. To increase the implementation of climate change adaptation measures, two more conceptual approaches were developed by the researcher in addition to the initially hypothesised partnering approach. These additional conceptual approaches involved policy development by housing associations vis-à-vis climate change adaptation measures and collaboration with external actors who face the same challenges in order to enhance efficiency in solving these issues together. The feasibility of the three conceptual approaches was verified by means of a SWOT analysis performed with practitioners from housing associations and construction companies as well as external players such as water authorities, insurance companies and municipalities. The results of the SWOT analysis made it clear that single-pronged conceptual approaches are unlikely to be successful because they involve serious weaknesses or threats. A combination of conceptual approaches is much more likely to remove the barriers that obstruct the implementation of climate change adaptation measures. The conceptual approaches were therefore combined and renamed as implementation strategies. In on-line questionnaires carried out among all Dutch housing associations, it was assessed if the housing associations found it likely that these strategies would indeed lead to the implementation of climate change adaptation measures. In general, the respondents assessed the feasibility of all strategies as unlikely to neutral. There was no strategy that clearly stood out as more feasible for the implementation of climate change adaptation measures. However, a considerable number of housing associations assessed one or more implementation strategies positively and saw opportunities for the implementation of measures, albeit framed differently, such as measures to increase energy-efficiency or enhance comfort. Conclusion Based on the findings outlined above, the answer to the main research question is: Partnering in construction can increase the implementation of climate change adaptation measures in dwellings owned by housing associations, when it is understood as a catalyst for information-sharing and increased efficiency in the construction process. By looking for shared interests between housing associations and the construction sector, the chances of implementing adaptation measures increase. However, if other stakeholders are involved as well, and if housing associations embed climate change adaptation in their policy guidelines, the likelihood of implementation would increase even more. Although none of the implementation strategies stood out clearly as the strategy most likely to result in the implementation of climate change adaptation measures, a considerable number of housing associations assessed various implementation strategies positively. If the construction process becomes more network-based, which is the case when a partnering approach is adopted, many more parties can become involved and contribute to the implementation of climate change adaptation measures. In such a situation, it no longer matters who introduces the subject during the plan development and construction process, as long as it ends up there and action is taken. To implement these measures more easily, the framing is very important. Climate change adaptation is not enough reason in its own right to begin implementing measures. Insulation to prevent overheating in the summer is considered an ‘extra’ measure - the necessity of which is still questioned by policymakers, for example. However, if the same measure is framed as an energy-saving measure, it is also a cost-cutting measure, which increases the likelihood that policymakers will start making plans to implement it! Scientific implications of the results This thesis has contributed to the development of governance tools to increase the implementation of climate change adaptation measures in dwellings, while current adaptation strategies predominantly target the national or local levels of the built environment. Moreover, this thesis has examined the adoption of partnering as a project delivery method and a governance tool with which to bridge the theoretical fields of network governance and integrated construction and maintenance processes. It extends the palette of governance tools that traditionally consists of information tools, tools relating to the division of property rights, incentives and regulatory tools. It has proven that housing associations can successfully adopt partnering approaches. As such, partnering is a feasible approach by which to increase the implementation of innovative measures such as climate change adaptations. Practical implications The assessment of the five implementation strategies showed that adapting housing for climate change has a low priority as a separate policy field. It is a relatively new area for policymakers, so they may be reluctant to believe that measures are likely to be implemented. Moreover, many other topics may take a higher priority for them, such as improving energy-efficiency and thereby also the affordability of dwellings, and/or preparing the dwellings for an ageing population. In the literature on climate change adaptation, it is suggested that mainstreaming climate change adaptation is the best course, which implies attaching the adaptation policy to existing policy frameworks. This would make policymakers aware of the topic of climate change adaptation and they could look for synergies between measures that were already planned and measures related to climate change adaptations. The refurbishment and maintenance process of housing associations provides opportunities for the mainstreaming of adaptation measures. Housing associations are facing an ageing stock that needs to be improved if it is to continue to meet the ever increasing basic requirements of tenants in terms of quality and comfort and increasingly strict energy-efficiency standards. Since climate change is occurring gradually, there is still time to adapt the building stock gradually, in step with the renovation and maintenance cycles of the housing associations. Bringing in external players, especially municipalities and water authorities, would appear to be a highly feasible approach, given their shared interest in the quality of life in local areas. Bringing together the construction partners requires governance tools that inform them of the benefits of partnering. Particularly if construction companies are to be responsible for the renovation and the maintenance for the rest of the service life of the dwellings, they could focus on improved design solutions that aim to create resilient dwellings, and/or using materials that would be less affected by the effects of climate change. The role of tenants in the implementation of climate change adaptations is primarily that they might exert ‘bottom-up’ pressure by requesting action from housing associations. But for this to happen, they would likely need to be informed about the effects of climate change on their dwellings and/or neighbourhoods, in order for them to be motivated to ensure that their homes are climate change resilient.